Promoting Productive Uses of Electricity in Rural Areas of Peru : Experience and Lessons Learned - Finucane, James; Bogach, V. Susan; Garcia, Luis Enrique (World Bank, Washington, DC, 2016)
The Government of Peru is committed to improving rural electrification coverage, aiming to increase rural coverage from an estimated 55 percent at the end of 2010 to 88 percent by 2020. To achieve this goal, the Directorate General of Rural Electrification (DGER) of the Ministry of Energy and Mines (MEM) has been implementing and executing the National Plan for Rural Electrification, prepared annually, based on the 2006 Rural Electrification Law, to extend service and attract participation of the population, local governments and electricity distribution companies. Within this program, the World Bank (WB) and Global Environmental Facility (GEF) are supporting the Directorate of Competitive Funds (DFC) of the DGER in the implementation and execution of the Rural Electrification (RE) Project, initiated in July 2006 and the Second Rural Electrification Project initiated in July 2011, to assist electricity distribution companies to implement rural electrification. Among the activities underway in the first RE Project is the implementation of a pilot program to develop the productive use of electricity, promoting opportunities for income generation in rural areas. This report provides an early assessment of the productive uses of electricity in Peru under the RE Project.